Does Intersectional Training Endure? Examining Trends in a Global Database of Women's and Gender Studies Graduates (1995-2010) - Berger, Michele Tracy (Atlantis, 2017)
The undergraduate experience remains a cornerstone in the foundation of Women’s and Gender Studies yet scholars know little about how graduates retain and demonstrate highly valued skills and concepts like intersectionality. This paper intervenes by answering the questions: How does intersectionality show up in graduates’ reflections on their training? How do graduates utilize intersectional thinking in their personal and professional lives? Drawing on quantitative data from a large, institutionally diverse and global survey of women’s and gender studies graduates, I demonstrate that intersectional training does endure and that graduates draw on intersectional concepts in the personal and professional life, in complex ways, long after graduation.